Association between Metarhizium anisopliae sensu lato and cypermethrin to control Rhipicephalus microplus - de Paulo, Jéssica Fiorotti; Ferreira, Julie Rhanna Tavares; Marciano, Allan Felipe; de Freitas, Maria Clemente; Rodrigues, Caio Junior Balduino Coutinho; Camargo, Mariana Guedes; Angelo, Isabele da Costa; Bittencourt, Vânia Rita Elias Pinheiro; Gôlo, Patrícia Silva (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. de Paulo J.F., Ferreira J.R.T., Marciano A.F., de Freitas, M.C. Coutinho-Rodrigues C.J.B., Camargo M.G., Angelo I.daC. Bittencourt V.R.E.P., Gôlo P.S. [Association between Metarhizium anisopliae sensu lato and cypermethrin to control Rhipicephalus microplus.] Associação de Metarhizium anisopliae sensu lato e cipermetrina para o controle de Rhipicephalus microplus. Revista Brasileira de Medicina Veterinária, 38(Supl.3):85-90, 2016. Departamento de Parasitologia Animal, Anexo 1, Instituto de Veterinária, Universidade Federal Rural Rio de Janeiro, BR 465 Km 47, Seropédica, RJ 23890-000, Brasil. E-mail: patriciagolo@gmail.com Rhipicephalus microplus is responsible for large economic losses in Brazilian livestock. In order to control this arthropod, the indiscriminate use of chemical products may be widely used, leading to damages to the environment, animals and humans, besides contributing to the appearance of resistant tick populations. The use of chemicals associated with biological entomopathogens drives an alternative to increase the effectiveness of tick control and reduce de damage caused by the inappropriate use of chemicals. Accordingly, the aim of the present study was to evaluate the efficiency of Metarhizium anisopliae and cypermethrin association on immature stages of R. microplus ticks. The groups were exposed by immersing the egg mass and larvae in 1 ml of fungal aqueous suspension, cypermethrin solution, cypermethrin associated to the fungal suspension and Tween 80 0.1% (v/v) (control). The biological parameters evaluated were: larval hatching percentage and larval mortality percentage. It was observed that both the fungus in a low concentration (106 conidia mL-1) or cypermethrin in a low concentration (25 ppm) were not able to change the biological parameters in comparison to the control group. Despite this, when associated the fungus at 106 conidia mL-1 with cypermethrin in a low concentration, together they were able to reduce larval hatching percentage and increase mortality in comparison to the single use of fungus or cypermethrin. Accordingly, it is concluded that the association of M. anisopliae with cypermethrin is a promising alternative to control of immature stages of R. microplus.